Pattern of Aeroallergen Sensitization and Quality of Life in Adult Thai Patients With Allergic Rhinitis - Katel, Puspalal; Pinkaew, Bannapuch; Talek, Kanokporn; Tantilipikorn, Pongsakorn (Frontiers in Allergy, 2021)
The prevalence of allergic rhinitis (AR) is steadily rising in the Thai population, causing a major impact on the quality of life (QoL). Enhancing knowledge on common aeroallergens in the local setting helps in the appropriate prevention and management of AR. In this study, the demographic characteristics, clinical data, aeroallergen sensitization pattern, allergic symptoms, visual analog scale (VAS) score, and QoL are described. We evaluated the association between VAS, QoL, and severity of symptoms, except the aeroallergen sensitization pattern. We retrospectively reviewed the medical records of adult AR patients with a positive skin prick test (SPT) for at least one aeroallergen from January 2018 to May 2020. Standard descriptive and inferential statistics were used for analysis. A total of 366 patients were enrolled. Indoor aeroallergen sensitization and outdoor aeroallergen sensitization were observed in 32% and 7.9% of patients, respectively. Mono-sensitization was noted in 16.9% of patients, while poly-sensitization was noted in 83.1% of patients. Mites (65%) and sedge (39.3%) were the most common indoor and outdoor allergens. Nasal obstruction (74.6%), runny nose (63.7%), and nasal itchiness (61.5%) were the primary symptoms affecting the QoL. The association between VAS and symptom scores showed a trend of association with AR severity (Allergic Rhinitis and its Impact on Asthma [ARIA] classification) and VAS. AR has a significant effect on QoL in all domains of the validated generic (short-form-36, SF-36) and specific (rhino-conjunctivitis QoL questionnaire, Rcq-36) questionnaires. Mite and sedge remain the most common indoor and outdoor aeroallergens. The pattern of sensitization and number of aeroallergens were not associated with AR based on the ARIA guidelines. Meanwhile, symptoms of patients affected the QoL and VAS scores, which can be used as a quick and reliable tool for monitoring and stepping up or stepping down the treatment according to the next-generation guidelines. AR has a significant impact on the QoL of adult Thai patients.